The effect of phase I therapy on the clinical parameters, VSC levels, and RBS levels in chronic periodontitis patients with diagnosed diabetes - Pushpalatha Tummakomma; Satyanarayana Durvasula; Neeharika Soorneedi; Khurramuddin Mohammed; Mohammed Abidullah; Syed Nazia Tabassum (Wolters Kluwer Medknow Publications, 2020)
Introduction: The relationship between chronic periodontitis and type 2 diabetes mellitus (DM) is bidirectional. Halitosis or oral malodor has an effect on psychological and social life of persons, and is seen in individuals with diabetes. Aims and Objectives: The aim of this study was to find out the effect of phase I therapy on the clinical parameters, volatile sulfur compound (VSC) levels, and random blood sugar (RBS) levels in chronic periodontitis patients with diagnosed DM. Materials and Methods: Our study included 80 patients with diabetes and chronic periodontitis. We collected subgingival plaque samples at 1 week and 1 month after scaling and root planing. The parameters measured were probing pocket depth and clinical attachment level for all the teeth at four sites per each tooth. RBS levels were recorded for all the patients. Malodor was measured with Tanita Breath Checker (Tanita India Private Limited, Mumbai, Maharashtra, India). Results: We found a statistically significant reduction in clinical parameter levels, VSC levels, and N-benzoyl-dl-arginine-2-naphthylamide (BANA) levels in both the groups from baseline to 4 weeks with highest levels in diabetic chronic generalized periodontitis (CGP) and lowest in nondiabetic CGP at baseline. The mean intergroup comparison of BANA levels was statistically significant at all intervals of time between the two the groups. Conclusion: There is a significant correlation observed between oral malodor levels, RBS, and clinical parameters in the diabetic group.